Pengaruh Permainan Lempar Tangkap Bola Terhadap Koordinasi Mata Tangan Dan Kaki Siswa Tunagrahita - Indra Setiawan; Dwi Gansar Santi Wijayanti; Mohamad Annas; Agus Pujianto (Indonesian Journal for Physical Education and Sport, 2024)
There are still many students ability to carry out activities that require the cooperation of muscles, nerves and other systems is caused by a lack of eye, hand and foot coordination. This research was to determine the effect of throwing and catching a ball on eye, hand and foot coordination of mentally retarded students at SLB Negeri Ungaran. This type of research is experimental. The data collection technique used is the test and measurement. In the pretest results, there were students who got the lowest score with a score of 5, the highest score with a score of 10, the total score was 53, the average score was 6.63 and the standard deviation value was 1.685. The posttest for eye, hand and foot coordination, there were students who got the lowest score with a score of 8, the highest score with a score of 15, the total score was 87, the average score 10.88 and the standard deviation value was 2.031. Based on the results of the t test between the pretest and posttest groups, the ability to throw and catch the ball showed a value of 0.000 <0.05, which means the hypothesis raised in this study (Ha) was accepted. The results of data analysis show that the ball throwing and catching training program has a significant influence on eye, hand and foot coordination abilities